Targeted Advertising and Social Status - Nick Vikander (Tinbergen Institute, 2011)
This paper shows how a firm can use non-targeted advertising to exploit consumers' desire for social status. A monopolist sells multiple varieties of a good to consumers who each care about what others believe about his wealth. Advertising allows consumers both to buy different varieties and to recognize them when others buy. In equilibrium, the firm advertises each variety to those who will buy but also to all poorer consumers who will not, so that they understand what having the goods signals. If concern for status is sufficiently high, then the firm will only place a single variety on the market.
Keywords: M37; L12; L15; 330; advertising; targeting; social status; Werbewirkung; Konsumentenverhalten; Sozialer Status; Konsumtheorie